2021
DOI: 10.1080/19490976.2021.1918993
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive small molecules produced by the human gut microbiome modulate Vibrio cholerae sessile and planktonic lifestyles

Abstract: Humans live in symbiosis with a diverse community of microorganisms, which has evolved to carry out many specific tasks that benefit the host, including protection against invading pathogens. Within the chemical diversity of the gastrointestinal tract, small molecules likely constitute chemical cues for the communication between the microbiota and pathogens. Therefore, we sought to investigate if molecules produced by the human gut microbiota show biological activity against the human pathogen Vibrio cholerae.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Metabolite produced by gut microbiota also plays an important role in the resistance of V. cholerae. Bioactive compounds generated by gut microbiota impede V. cholerae motility and its ability to penetrate mucin [108]. Colibactin, a genotoxin generated by Escherichia coli, could inhibit the colonization of V. cholerae and is associated with the better prognosis of cholera patients [109].…”
Section: Cholera 41 Interaction Of Gut Microbiome and Choleramentioning
confidence: 99%
“…Metabolite produced by gut microbiota also plays an important role in the resistance of V. cholerae. Bioactive compounds generated by gut microbiota impede V. cholerae motility and its ability to penetrate mucin [108]. Colibactin, a genotoxin generated by Escherichia coli, could inhibit the colonization of V. cholerae and is associated with the better prognosis of cholera patients [109].…”
Section: Cholera 41 Interaction Of Gut Microbiome and Choleramentioning
confidence: 99%
“…Studies have confirmed that the body’s homeostasis and the intestinal immune function depend on the balance of bacteria in different degrees, and once this balance is destroyed, it will lead to the occurrence of related diseases ( Bruellman and Llorente, 2021 ; Han et al., 2021 ; Khan et al., 2021 ; Shute et al., 2021 ; Sun et al., 2021 ; Deng et al., 2022b ; Hu et al., 2022 ). The dysregulation of gut microbiota can be caused by many factors, such as age ( Du et al., 2021 ; Janiak et al., 2021 ), lifestyle ( Pauer et al., 2021 ; Shin et al., 2021 ), dietary habits ( Neumann et al., 2021 ; Tap et al., 2021 ; Yu et al., 2021 ), immunity ( Foley et al., 2021 ; Hosseinkhani et al., 2021 ) and the use of antibiotics ( Kang et al., 2021 ; Mcdonnell et al., 2021 ; Strati et al., 2021 ; Vicentini et al., 2021 ).…”
Section: Intestinal Microbiotamentioning
confidence: 99%
“…Microbiota-mediated resistance against pathogenic bacteria occurs through indirect or direct mechanisms, such as nutrient or niche competition and antimicrobial compound production [6][7][8] . More importantly, various studies have explored that molecules produced by gut microbiota or metabolites derived from specific microbiota members could mitigate pathogens' virulence, protect mice from infection induced by enteric pathogens and restore the native community after the disruption with antibiotics [7,[9][10][11] .…”
Section: Introductionmentioning
confidence: 99%